A Critique on the Book The Effect of Classic Persian Literature in the Contemporary Story Writing - Seyed Ali Qasemzade (پژوهش‌نامۀ انتقادی متون و برنامه‌های علوم انسانی)
One of the fundamental questions in the literature of the new story writing in Iran is the extent of the linkage with classical Persian literature. The importance of this question becomes apparent when most critics and researchers in the field of fiction, novel, and short stories consider it as the imported art (Western), and it is believed that the entry and expansion of new fiction to Iran should be based on the same western art attitude and non-native phenomenon. It is clear that in the light of such an attitude, expecting the benefit and relationship of the Iranian storyteller with his literary past looks awesome and awkward. The Effect of Classic Persian Literature in Contemporary Story Writing by Masoume Sadeqi, an answer to the serious rejection of the novelty of the novel and the new Iranian story Relying on the three novels Suvashoon, Missing Salooch, and Fire without Smoke, while rejecting the prevailing view, Reveals the Iranian writers' influence on the style and language of Persian classical literature. The present study, by revising this work in a descriptive-analytical manner, concluded that in spite of the writer's admirable effort to prepare and collect intelligible information and intertextual representations of selected novels with some basic objections and unbalanced thematic propositions, the data analysis and the final interpretation of novels are confronted. An insulting approach to the whole and the whole of this attitude requires a serious review in the book.